San'ani's View on Women Authority in the Book of Subul al-Salam | ولاية المرأة عند الصنعاني في سبل السلام - Fatihunnada Anis; Ulfa Fauziah (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2019)
At the beginning of the twentieth-century, many discussions arose about the role of women in society or in the social sphere. One characteristic of these discussions is the question